Ruminal degradation of dietary protein in steers fed lasalocid - R.H. Wessels; Evan C. Titgemeyer; Jean G. St. (Kansas Agricultural Experiment Station Research Reports, 1994)
A trial was conducted to investigate the effect of lasalocid (Bovatec®) on ruminal degradation of dietary protein in Holstein steers. Five ruminally and duodenally cannulated steers (305 kg) were fed a corn-alfalfasoybean meal diet (17% CP), with or without lasalocid, in a three period, switch-back experiment. Ruminal pH, ammonia, volatile fatty acids, and amino acid and peptide concentrations were unaffected by lasalocid. Lasalocid reduced (P<.05) ruminal protease activity by 15%, but did not change deaminase activity. Digestibilities of dry matter, organic matter, fiber, and crude protein were similar between treatments. Intestinal flows of microbial and feed crude protein fractions, as well as amino acids, remained unchanged when lasalocid was fed. Thus, in this experiment, lasalocid failed to decrease feed protein degradation in the rumen and, therefore, was unable to increase the supply of crude protein or amino acids to the small intestine.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Ionphore; Lasalocid; Protein degradation; Microbial protein; Amino Acids; Ruminants